The 5-minute sports medicine consult - Bracker, Mark D. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"This new addition to The 5-Minute Consult Series is a clinically oriented quick consult reference for sports medicine. For the first time, common sports-related problems faced by primary care practitioners are thoroughly and concisely presented in the famous fast-access 5-Minute Consult format.Chapters on musculoskeletal problems cover basics; diagnosis; acute treatment, including on-field management; long-term treatment, including rehabilitation and referrals; and commonly asked questions. Other chapters address the special populations of children, adolescents, females, geriatric athletes, and disabled athletes and general medical problems in athletic individuals. Appendices include clinical care algorithms, a guide to the preparticipation examination, and patient education handouts"--Provided by publisher.